Penentuan Komoditas Unggulan untuk Ketahanan Pangan di Kawasan Metropolitan PEKANSIKAWAN - Fiora Helmi; Ernan Rustiadi; Bambang Juanda; Sri Mulatsih; Dewi Diniaty (Research and Development Agency Ministry of Home Affairs, 2025)
Food security is a critical aspect of regional development, particularly in metropolitan areas that function as centers of consumption, production, and distribution. This study aims to identify leading food commodities in the PEKANSIKAWAN Metropolitan Area of Riau Province, which includes Pekanbaru City, Kampar Regency, Siak Regency, and Pelalawan Regency, and to provide recommendations for strengthening regional food security. The research employed Location Quotient (LQ) and Shift Share Analysis (SSA) to examine comparative and competitive advantages across the four regions. The analysis identified four key commodities: poultry meat in Pekanbaru City, aquaculture fish in Kampar Regency, rice and onions in Siak Regency, and agroindustry-based rice and fish in Pelalawan Regency. These commodities form a complementary system that enhances interregional synergy and food supply resilience. The findings indicate that optimizing interregional linkages through collaborative investment, integrated supply chains, and food system clusters is essential to address both production disparities and consumption needs. The conclusion emphasizes that the metropolitan scale provides unique opportunities to combine local strengths into a coherent regional food system, which can better support the availability, accessibility, and stability of food. Policy implications highlight the need for strategic investment in irrigation, cold chain logistics, and digital market platforms, alongside institutional strengthening through farmer cooperatives, financial access, and capacity building. The study contributes scientifically by integrating territorial analysis with quantitative methods in a metropolitan context, offering both theoretical enrichment for food security literature and practical guidance for regional policymakers.